2013
DOI: 10.1007/s00586-013-3005-0
|View full text |Cite
|
Sign up to set email alerts
|

Zero-P: a new zero-profile cage-plate device for single and multilevel ACDF. A single Institution series with four years maximum follow-up and review of the literature on zero-profile devices

Abstract: Purpose To analyze the prospectively collected data in a series of patients treated with single-or multilevel ACDF with a stand-alone, zero-profile device, focusing on clinicoradiological outcome, complications and technical hints, and to review the literature on such new devices. Methods Eighty-five patients harboring symptomatic DDD underwent ACDF with the Zero-P cage-plate: 29 at 1-level and 56 at 2-4 levels (total 162 devices). In the multilevel group, 9 patients received a combination of Zero-P and stand-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 41 publications
1
48
0
1
Order By: Relevance
“…19 , 21 , 22 The AC, which supplements the advantages and disadvantages of the aforementioned CP and SC, is gradually becoming more widely used. [1][2][3][4][5][6] Vanek et al 1 conducted a minimal 2-year prospective comparative study on the Zero-P spacer. Compared with the CP, there were no differences between the 2 groups for neck disability index, Cobb coronal value, and the presence of dysphagia; although the Cobb sagittal values differed up to 6 weeks, no differences were reported beyond that point.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…19 , 21 , 22 The AC, which supplements the advantages and disadvantages of the aforementioned CP and SC, is gradually becoming more widely used. [1][2][3][4][5][6] Vanek et al 1 conducted a minimal 2-year prospective comparative study on the Zero-P spacer. Compared with the CP, there were no differences between the 2 groups for neck disability index, Cobb coronal value, and the presence of dysphagia; although the Cobb sagittal values differed up to 6 weeks, no differences were reported beyond that point.…”
Section: Discussionmentioning
confidence: 99%
“…2 , 3 Because these shortcomings of the SC and anterior cervical plate (ACP) are being improved upon, the use of ACs is gradually increasing. [1][2][3][4][5] Most authors have indicated that radiological and clinical outcomes of ACs are similar to those of cages with plates (CPs) and have particularly emphasized the point about the decreased occurrence of postoperative dysphasia. [1][2][3][4][5][6] ACs maintained comparable stability with CPs in one biomechanical study, but ACs showed a higher range of motion in fl exion/extension 7 ; in contrast, other articles reported that ACs lack multilevel stability.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Barbagallo et al mentioned that SF-36 and NDI showed a statistically significant improvement and mean arm pain VAS score deterioration on zero-profile cage-plate device. Fusion rate was estimated over 90% and dysphagia at 15.5% without any device-related complication (36). For pain and disability, NDI is said to be the most valid and responsive measure of improvement after surgery for neck and arm pain.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances including low profile, integrated interbody cages have been developed in order to obviate the need for anterior plating with the goal of reducing plate-related morbidity. A number of biomechanical studies have shown that an anchored cage design with integrated screws afforded biomechanical stability comparable to that of the standard interbody cage with anterior plate [5]. Though long term studies are limited, several integrated low profile designs have been shown to have decreased rates of dysphagia compared to standard anterior plating systems [23].…”
Section: Anterior Platingmentioning
confidence: 99%